Paradigm Shift Of Limited Liability Company Post Job Creation Law - Iriantoro, Agung (Fox Justi : Jurnal Ilmu Hukum, 2024)
The limited liability company law in Indonesia has undergone substantial modifications due to Law Number 11 of 2020 on Job Creation. One important development is the introduction of the idea of an individual limited liability company. The previous model of PT as a capital partnership has been replaced by this new model, which allows its formation by an individual. As a capital partnership, the Limited Liability Company faces a paradigm shift with the enactment of the Job Creation Law. The question is, how will this transition occur? How will this change in thinking affect the level of certainty that stakeholders, including business actors, have in the law? Conceptual and statutory approaches are used in this research as part of the normative legal research process. The research findings show that the paradigm shift of the PT has far-reaching consequences for several areas of corporate law, including limited liability, segregation of wealth, and corporate governance. There are theoretical and practical barriers to formally establishing micro and small businesses that the amendment seeks to remove. To maintain the consistency of the entire PT legal system, it is necessary to harmonize the Job Creation Law, UUPT, and other implementing regulations.